Virtual reality versus conventional clinical role-play for radiographic positioning training: A students' perception study. Issue 1 (February 2020) - Sapkaroski, D.; Mundy, M.; Dimmock, M.R.
Abstract: Introduction: Simulated learning environments (SLEs) are commonly utilised by educational institutions. The aim of this study was to assess if students perceptions varied relating to the effectiveness of either a virtual reality (VR) simulation or traditional clinical role-play scenario in developing radiographic hand positioning skills. Methods: A split-cohort study was performed with Year 1 Undergraduate Radiography students (n = 76). Students were randomly assigned to undertake training for radiographic hand positioning tasks using either the CETSOL VR Clinic software (Group 1) or traditional clinical role-play (Group 2). Following completion of their positioning training, students' perceived impact of the SLE on developing practical and technical skills were assessed using a 5-point Likert scale questionnaire and free text option. Results: Quantitative student perception scores indicated no significant difference between the two simulation modalities, the mean agreement scores (combined strongly agree + agree) for Groups 1 and 2 were 74.8% and 83.8%, respectively, where χ2 (4, n = 66) = 9.5, p-value = 0.394. Key themes expressed by students following a thematic analysis were "engagement with the learning environment, positioning practice and comparability to clinical practice. Conclusion: The perceptions of novice students in training for radiographic hand positioning tasks, using either a VR SLE or clinical role-play scenario, did not differ. There was a strong similarity in common themes, however, a key point of difference identified was the benefit of repetition afforded by the VR simulation, in contrast to the need for more time using traditional role-play in a constrained laboratory setting. Implications for practice: The lack of difference in student perceptions between VR and clinical role-play training, could offer a different approach to clinical training which is easily accessible and allows users to correct mistakes at their own pace.